2009
DOI: 10.1128/mcb.00197-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Rb1 Pathway Leads to Overexpression of mTor, Constitutive Phosphorylation of Akt on Serine 473, Resistance to Anoikis, and a Block in c-Raf Activation

Abstract: Atk can be activated by two independent phosphorylation events. Growth factor-dependent phosphorylation of threonine 308 (Akt-308) by phosphatidylinositol 3-kinase-dependent PDK1 leads to activation of mammalian target of rapamycin (mTor) complex 1 (TORC1) and stimulation of protein synthesis. Phosphorylation on serine 473 (Akt-473) is catalyzed by mTor in a second complex (TORC2), and Akt-473 phosphorylates Foxo3a to inhibit apoptosis. Accumulation of both phosphorylated forms of Akt is frequent in cancer, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…However, in primary cells, we found that Erk activation was not required for Ras induction of ZEB1 (ref. 44). Thus, the mechanism through which Ras induces ZEB1 is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in primary cells, we found that Erk activation was not required for Ras induction of ZEB1 (ref. 44). Thus, the mechanism through which Ras induces ZEB1 is still unresolved.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were cultured in DMEM with 10% heat-inactivated fetal bovine serum 13 . Ras-TKO MEFs were created by infection with a V12 Ras retrovirus as described 44 . The resulting cells were characterized with regard to Ras expression by western blot, and Ras activity was carried out by using the EZ-Detect Ras Activation Kit (Pierce Biotechnology, Rockford, IL) GST fusion protein containing the Ras-binding domain of Raf 44 .…”
Section: Methodsmentioning
confidence: 99%
“…The cells were cultured in DMEM with 10% heat-inactivated fetal bovine serum (26). Ras-triple knock-out (TKO) MEFs were created by infection with a V12Ras retrovirus and characterized with regard to Ras expression and activation as described in detail previously (27).…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, our results suggest that induction of ZEB1 in response to Rb1 family mutation is required to maintain repression of cdk inhibitors, which in turn allows for immortalization and loss of cell contact inhibition when the Rb1 family is mutated in TKO MEFs. Ras Causes Superinduction of ZEB1 in TKO MEFs-Introduction of V12Ras into TKO MEFs to create Ras-TKO MEFs has been described previously (6,27). Loss of function of all Rb1 family members is required to prevent oncogene-induced senescence in response to Ras, and accordingly Ras-TKO MEFs are tumorigenic when injected into nude mice (6).…”
Section: Induction Of Zeb1 Is Required To Maintain Repression Of Cdk mentioning
confidence: 99%
“…It was also demonstrated that the promotion of the viability of detached malignant intestinal epithelial cells involves the sequential activation of Ras, RhoA, and protease Calpain, leading to the degradation of Beclin-1, a key regulator of autophagy (Yoo et al, 2010). Moreover, the mutation of Rb1 inactivates c-Raf/Erk and phosphorylates Akt at site serine 473 by forming mTOR complex 2 (mTORC2) in mouse embryonic fibroblasts (MEFs), leading to anoikis resistance (El-Naggar et al, 2009). Similarly, activation of the PI3K/Akt2 pathway mediates anoikis resistance in prostate carcinoma cells with reduced mitochondrial DNA (mtDNA) content (Moro et al, 2009).…”
Section: Anoikis Related Signaling Pathways In Solid Tumorsmentioning
confidence: 99%